Pemenuhan Tenaga Kesehatan di Indonesia Melalui Rekrutmen PPPK di Kementerian Kesehatan - Dianita Rahmawati; Eko Sakapurnama (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2023)
Recruitment of Government Employees with Employment Agreements (PPPK) is a strategic step by the government in fulfilling manpower for certain positions in the public sector. PPPK recruitment held in the last two years has become a hot topic because of differences with the concepts promoted in the State Civil Apparatus Law with its implementation. In this article, we contribute to the literature by describing the PPPK recruitment system in 2022, especially for health workers in one of the government agencies, namely the Ministry of Health. In the first step, we explained about determining the needs of health workers in the year of creation of this article. The next step, we describe the PPPK recruitment of health workers with a closed system, where participants come from health workers who have worked in government-owned health agencies and are closed to the public. From the author's observations, we that this recruitment system has not optimally overcome the crisis of health workers that occurs and is more as a conversion of honorary workers with strict selection. Approximately 7,800 Non-ASN (honorary) employees were selected for the 5,322 formations offered, leaving 944 formations unfilled. But despite it all, when viewed from the honorary problem that does not end, the PPPK with this scheme actually provides a solution in the form of an affirmation policy, which is a more partial policy for those who meet the criteria. Especially considering that non-ASN health workers, whose number is currently more than twenty-three thousand people, their existence is an important asset that needs to be considered for their status and position. Health workers are trained professionals whose certainty of existence is an important key in health services in Indonesia.